Improving medication titration in heart failure by embedding a structured medication titration plan. (1st December 2016) - Hickey, Annabel; Suna, Jessica; Marquart, Louise; Denaro, Charles; Javorsky, George; Munns, Andrew; Mudge, Alison; Atherton, John J.
Abstract: Background: To improve up-titration of medications to target dose in heart failure patients by improving communication from hospital to primary care. Methods: This quality improvement project was undertaken within three heart failure disease management (HFDM) services in Queensland, Australia. A structured medication plan was collaboratively designed and implemented in an iterative manner, using methods including awareness raising and education, audit and feedback, integration into existing work practice, and incentive payments. Evaluation was undertaken using sequential audits, and included process measures (use of the titration plan, assignment of responsibility) and outcome measures (proportion of patients achieving target dose) in HFDM service patients with reduced left ventricular ejection fraction. Results: Comparison of the three patient cohorts (pre-intervention cohort A n = 96, intervention cohort B n = 95, intervention cohort C n = 89) showed increase use of the titration plan, a shift to greater primary care responsibility for titration, and an increase in the proportion of patients achieving target doses of angiotensin converting enzyme inhibitors/angiotensin receptor blockers (ACEI/ARB) (A 37% vs B 48% vs C 55%, p = 0.051) and beta-blockers (A 38% vs B 33% vs C 51%, p = 0.045). Combining all three cohorts, patients not on target doses when discharged from hospital were more likely to achieve target doses of ACEI/ARB (p < 0.0001) and beta blockers (p < 0.0001) within six months if they received a medication titration plan. Conclusions: A medication titration plan was successfully implemented in three HFDM services and improved transitional communication and achievement of target doses of evidence-based therapies within six months of hospital discharge.